The Eighteen Benedictions and the Minim before 70 CE - Instone-Brewer, David (The journal of theological studies, 2003)
The wording of one version of the Eighteen Benedictions, which is preserved in a Geniza fragment (T‐S K27.33b), appears to assume that the Temple is still standing, in two lines which are usually not printed. Other features of this version also suggest that it preserves wording which originates from the Second Temple period. It also includes the curse of the Minim which is traditionally regarded as a Jabnean addition, but there is evidence that the curse had an earlier origin, and the wording of the curse is found to be a criticism of the Sadducean priesthood.